2011
DOI: 10.1002/app.34472
|View full text |Cite
|
Sign up to set email alerts
|

Covulcanization of LLDPE/EMA blends using dicumyl peroxide

Abstract: The effect of dicumyl peroxide (DCP) content on the gel fraction, mechanical, dynamic mechanical, and thermal properties of linear low-density polyethylene (LLDPE)/ethylene-co-methyl acrylate (EMA) blends were studied. Gel content of the blends increases with increasing DCP content, and EMA is more prone to crosslinking than LLDPE. Wide-angle X-ray diffraction (WAXD) and differential scanning calorimetry (DSC) were used to study the effect of DCP crosslinking on percent crystallinity and crystalline structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The crystallinity of the polymer decreases with increasing cross‐linking degree []. In a previous study, the cross‐linking degree of LDPE was improved by increasing the amount of dicumyl peroxide (DCP), which is commonly used as a cross‐linking agent []. Moreover, given that the molecular chains of the polymer form a continuous network structure through the cross‐linking reaction, intermolecular chain force is enhanced, and tensile strength is improved.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity of the polymer decreases with increasing cross‐linking degree []. In a previous study, the cross‐linking degree of LDPE was improved by increasing the amount of dicumyl peroxide (DCP), which is commonly used as a cross‐linking agent []. Moreover, given that the molecular chains of the polymer form a continuous network structure through the cross‐linking reaction, intermolecular chain force is enhanced, and tensile strength is improved.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, the elongation at break is improved in all cured samples including the control one which indicates improvement in interfacial strength (due to peroxide cross-linking) without sacrificing the elastic property of rubber. 28 However, as compared to the control sample, impact strength increases and tension set decreases significantly for DCP-treated sample where clay platelets are exfoliated in the dispersed EMA phase as well as the EMA is reinforced with partial cross-linked. From Table 4, it can also be seen that at constant DCP loading, mechanical properties increase with increasing clay content up to 5 wt%.…”
Section: Resultsmentioning
confidence: 91%
“…27 Borah et al recently have studied the effect of DCP curing on LLDPE/ethylene methacrylate (EMA) blends and reported that EMA exhibits superior cross-linking as compared to LLDPE. 28 At low peroxide content (0.3 wt%), mutual cross-linking of the elastomeric phase (EMA) as well as interface with low degree of modification of plastic phase (LLDPE) has been demonstrated. It has also been reported that at 0.3 wt% of DCP loading, the gel fraction of pristine LLDPE is 18%, whereas for pristine EMA (30% methacrylate content), it is 49.89%.…”
Section: Introductionmentioning
confidence: 99%
“…Materials LLDPE (LLT12) having a density of 0.926 g/cm 3 and MFI (melt flow index) 3.7 g/10 min, was obtained from Haldia Petrochemicals Ltd., India. Commercial grade of EMA, Elvaloy 1330 with 30 wt% of methyl acrylate and a melt flow index (MFI) of 3.0 g/10 min of DuPont, USA was supplied by NICCO Corporation Ltd., India.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled crosslinking of polymers has been found to improve creep, tensile properties, and mechanical stability at high temperature . Since crosslinking of polymer blends can generate interpenetrating polymer networks, it may improve the properties of the blends.…”
Section: Introductionmentioning
confidence: 99%